Evaluasi Manajemen Lingkungan Pengendalian Vektor Dalam Upaya Pemberantasan Penyakit Malaria di Kota Ternate - Rahmawati, Sari Lestari; Nurjazuli, Nurjazuli; Raharjo, Mursid (Jurnal Kesehatan Lingkungan Indonesia, 2012)
Background : Malaria is one tropical disease that continues spread to this day, lead to suffering of millions peoples in various parts of the world. In Indonesia, malaria is still one of the major health problems. Ternate city is one area in eastern Indonesia that has high endemicity. The reports of malaria from seven Puskesmas (Community Health Center) showed that rates of malaria per 1000 population (API) in 2010 was 6 ‰. There are three Puskesmas included in the HCI (High Case Incidence) that is the malaria-endemic areas with API rate >5/1000 population. These Puskesmas, among others Puskesmas Kalumpang (11 ‰), Puskesmas Gambesi (7 ‰) and Puskesmas Siko (6 ‰).This research aimed to evaluate the environmental management of vector control in effort of malaria diseaseeradication in Ternate City. This research was a descriptive research using a survey method. Population in this research were people who involved either directly or indirectly in the program of malaria eradication in DinkesTernate, some Puskesmas officers and related institutions. Data obtained in primary through interviews with questionnaires and secondary with archives study / documents / observation sheet.Methods : This research was a descriptive research using a survey method. Population in this research were peoplewho involved either directly or indirectly in the program of malaria eradication in Dinkes Ternate, some Puskesmasofficers and related institutions. Data obtained in primary through interviews with questionnaires and secondarywith archives study/documents/ observation sheet.Result : The results showed that implementation of malaria eradication in Health Department of Ternate City wasdone based on circumstances of the incidence of clinical malaria patient were reported and adjusted to the availablefunds. Evaluation results of vector control showed that Implementation of the environmental management covering an operational techniques aspect (middle categories), institutions aspect (middle categories), financing aspect (middle categories), regulation aspect (good categories) and participation of community aspect (middle categories).Conclusion : Conclusion of this research is environmental management of vector control in Ternate city includedmiddle category.Key words : Environmental Management, Vector Control, Malaria incidence.